2007
DOI: 10.1186/gb-2007-8-8-r173
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs show a wide diversity of expression profiles in the developing and mature central nervous system

Abstract: Background: MicroRNA (miRNA) encoding genes are abundant in vertebrate genomes but very few have been studied in any detail. Bioinformatic tools allow prediction of miRNA targets and this information coupled with knowledge of miRNA expression profiles facilitates formulation of hypotheses of miRNA function. Although the central nervous system (CNS) is a prominent site of miRNA expression, virtually nothing is known about the spatial and temporal expression profiles of miRNAs in the brain. To provide an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
291
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(310 citation statements)
references
References 63 publications
14
291
0
3
Order By: Relevance
“…In the mouse retina, these mature miRNAs are strongly expressed in photoreceptors, bipolar cells, and amacrine cells of the inner nuclear layer (INL) , while in zebrafish expression is more strongly photoreceptor-specific (Kapsimali et al, 2007). Expression of these miRNAs is reduced several-fold in rd1 mice where rod photoreceptors have fully degenerated, confirming that they are photoreceptor-enriched, though not entirely photoreceptor-specific.…”
Section: Mirnas Retinal Cell-specific Mirnasmentioning
confidence: 97%
See 2 more Smart Citations
“…In the mouse retina, these mature miRNAs are strongly expressed in photoreceptors, bipolar cells, and amacrine cells of the inner nuclear layer (INL) , while in zebrafish expression is more strongly photoreceptor-specific (Kapsimali et al, 2007). Expression of these miRNAs is reduced several-fold in rd1 mice where rod photoreceptors have fully degenerated, confirming that they are photoreceptor-enriched, though not entirely photoreceptor-specific.…”
Section: Mirnas Retinal Cell-specific Mirnasmentioning
confidence: 97%
“…Studies in zebrafish have also identified several miRNAs with cellspecific expression in retina (Kapsimali et al, 2007). Hundreds of different miRNAs are expressed in the retina, with several dozen showing substantially enriched expression in retina relative to the brain or peripheral tissues (Table 1).…”
Section: Mirnas Retinal Cell-specific Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The strikingly regulatory effects of miRNAs on the brain during development vary depending on developmental stages and/or the specific brain regions [10,[12][13][14], contributing to the balance between neural stem cell proliferation and differentiation, therefore directing neural cell fates and brain morphogenesis. In general, miR-124, miR-125b, miR-137, miR-7 are contributing to neuronal differentiation, whereas miR-134, miR-184 are effective in maintaining neural stem cells at the undifferentiated status [15,16].…”
Section: Mirnas In the Central Nervous System (Cns)mentioning
confidence: 99%
“…En effet, des neurones continuent à être générés dans le cerveau des vertébrés à l'âge adulte, à partir des cellules souches neurales. Une expression de miR-9 a été détectée dans les régions de neurogenèse du cerveau adulte chez le poisson zèbre et la souris [28,29]. miR-9 régulerait-il là aussi la dynamique de choix cellulaire ?…”
unclassified